Overview of the defifinitions of terrorism in international criminal law - Pék, Richárd Tamás (Magyar Rendészet, 2022)
Nowadays terrorism is one of the most dangerous, domestic and international security threat in the world. There are national, regional and global efforts in the field of counter-terrorism which are codified in international, regional and national criminal codes, treaties. Unfortunately and despite the seriousness of this threat there is no internationally accepted common definition of terrorism in the “global” international criminal law. At the level of regional and national treaties, in some parts of the criminal codes some types of terrorism are defined. Academic research and its results could be used at the legislation process, but this research has struggled to identify a widely accepted definition of terrorism. Hence we can find several definitions and typology of terrorism which could prove problematic for the legislators. This lack of common definition proves to be one of the main hurdles of effective cooperation among states and criminal authorities also having a negative impact on the effectiveness of counter-terrorism measures. My paper demonstrates in three chapters this definitional problem with regard to criminal law. In the conclusion I outline some proposals and probable directions of a new regulatory method in order to mitigate this problem through reaching an accepted common definition in legislations and criminal law.